Analysis Of The Profitability Of The Beef Cattle Business In Lolong Guba District, Buru Regency - Michel Johan Matatula; Arnold Ismael Kewilaa; Riri Sarfan (Journal Of Social Science (JoSS), 2024)
The beef cattle business will have a higher use value if the production factors can be used effectively and efficiently to obtain decent profits, thus ensuring the sustainability of the business for the welfare of farmers. This study was conducted with the aim of finding out the income, profitability, and factors that affect the income of the beef cattle business. The survey was carried out in Lolong Guna District, Buru Regency, which took place in August 2023. A total of 3 villages, namely Wanakarta, Waegeren, and Grandeng villages, were designated as sample villages, and 60 respondents were determined by purposive sampling with the criteria of having raised beef cattle for more than three years and selling livestock in the last year. Revenue and profitability analysis was carried out to determine the feasibility of the business, and multiple linear regression analysis was performed to determine the factors that affect revenue. The average revenue of the beef cattle business is Rp. 4,492,900 per year with a profitability value of 47.37%. Factors that affect the income of the beef cattle business are production costs, the number of livestock marketed, and the selling price of livestock. Meanwhile, livestock ownership does not affect income.